Fabrication and Adsorption Behavior of Magnesium Silicate Hydrate Nanoparticles towards Methylene Blue - Renyao Huang; Li He; Tao Zhang; Dianqing Li; Pinggui Tang; Yingying Zhao; Yongjun Feng (Nanomaterials, 2018)
Magnesium silicate as a high-performance adsorption material has attracted increasing attention for the removal of organic dye pollution. Here, we prepared a series of magnesium silicate hydrates (MSH) in a hydrothermal route, and carefully investigated the corresponding adsorption behavior towards methylene blue (MB) as well as the effect of surface charge on adsorption capacity. The results show that surface charge plays a key role in the adsorption performance of MSH for MB, a negative surface charge density follows the increase of Si/Mg feeding ratio from 1.00 to 1.75, and furthermore the higher negative charge favors the improvement of the adsorption capacity. Among four investigated samples (MSH = 1.00, 1.25, 1.50, and 1.75), MSH-1.75 has the highest negative surface charge and shows the largest adsorption capacity for MB. For example, the equilibrium adsorption quantity is 307 mg·g−1 for MSH-1.75, which is 35% higher than that of 227 mg·g−1 for MSH-1.00. Besides, for MSH-1.75, the as-prepared sample with negative charge exhibits ca. 36% higher adsorption quantity compared to the sample at the zero point of charge (pHZPC). Furthermore, magnesium silicate hydrate material with Si/Mg feeding ratio = 1.75 demonstrates the promising removal efficiency of beyond 98% for methylene blue in 10 min, and the maximum adsorption capacity of 374 mg·g−1 calculated from the Langmuir isotherm model.